Hello, letranger9000!
You don't mean "reciprocal" . . . You mean "inverse".
Good work!
Punchline: /
Do you know how to check your answer?
Evaluate or .
Either must simplify to
Multiply by
ta-DAA!
I don't have access to a teacher in the present moment, I just want to make sure I understand right. If I am wrong please point out where is my error, thank you.
f (x) = (2x+1) / (x-3)
y=(2x+1) / (x-3)
x=(2y+1) / (y-3)
x(y-3)=(2y+1)
xy-3x-2y=1
xy-2y=(3x+1)
y(x-2)=(3x+1)
y(x-2)/(x-2)=(3x+1)/(x-2)
y=(3x+1)/(x-2)
Hello, letranger9000!
You don't mean "reciprocal" . . . You mean "inverse".
Good work!
Punchline: /
Do you know how to check your answer?
Evaluate or .
Either must simplify to
Multiply by
ta-DAA!